SISTEMA DE APOIO À GESTÃO DE ÁREAS VERDES NA PRESERVAÇÃO PERMANENTE DE CORPOS HÍDRICOS URBANOS - Bressane, Adriano; Mochizuki, Patricia Satie; Roveda, José Arnaldo Frutuoso; Salvador, Nemésio Neves Batista (Universidade Federal de Santa Maria, 2016)
ABSTRACT The conservation of urban green areas is among the key strategies for achieving healthy and sustainable cities. However, the multiplicity of the involved factors requires an integrated analysis by means of a logical and structured procedure. Therefore, this article aims to present the proposal for a decision support system for the management of green areas in public domain, in areas of permanent preservation of urban water bodies. For its development, guidelines of the plannning method through scenarios were adopted, by which the aspects related to the problem and routing solutions were analysed. The main used materials correspond to the works of technical literature and legislation, raised through search terms along with bibliographic and legislative seats. From the analysis of these materials, we studied the actual functions of these areas of permanent preservation and the factors affecting their performance and protection. As a result, we obtained a structured model in key decision for the selection of the location alternatives and their function-space capability.

RESUMO A conservação de áreas verdes urbanas está entre as principais estratégias para o alcance de cidades saudáveis e sustentáveis. Entretanto, a multiplicidade de critérios envolvidos requer uma análise integrada por meio de um procedimento lógico e estruturado. Portanto, este artigo tem como objetivo apresentar a proposta de um sistema de suporte à decisão para gestão de áreas verdes de domínio público em áreas de preservação permanente de corpos hídricos urbanos. Para o seu desenvolvimento foram adotadas as diretrizes do método de planejamento por cenários, mediante o qual foram analisados aspectos correlatos ao problema e encaminhamento de soluções. Os principais materiais utilizados corresponderam às obras da literatura técnica e a legislação aplicada, levantados através de termos de busca junto aos acervos bibliográficos e bancos normativos. A partir da análise destes materiais foram estudadas as efetivas funções das referidas áreas de preservação permanente e os fatores intervenientes ao seu desempenho e proteção. Como resultado, obteve-se um modelo estruturado em chaves de decisão para seleção de alternativas locacionais e de sua aptidão espaço-funcional.
SUPPORT SYSTEM FOR MANAGEMENT OF GREEN SPACES IN PERMANENT PRESERVATION OF URBAN WATER BODIES
Keywords: decision support; permanent preservation area; green area of public domain; suporte à decisão; área de preservação permanente; área verde de domínio público